2011
DOI: 10.1155/2011/541831
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Gutta-Percha/Zinc-Oxide-Eugenol Sealer or Gutta-Percha/Epoxy Resin Sealer from Severely Curved Canals: An In Vitro Study

Abstract: The aim of this study was to compare the cleanliness of root canal walls after retreatment using two rotary retreatment files to hand instruments in severely curved canals obturated with gutta-percha and two different sealers. Single rooted mandibular premolars (n = 90) with root curvatures were instrumented and obturated with gutta-percha and an epoxy resin (Group 1, n = 45) or zinc oxide eugenol sealer (Group 2, n = 45). Following retreatment of the specimens (n = 15 ProTaper Universal Retreatment Files (Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
4
7
1
Order By: Relevance
“…Our results demonstrate that the apical third had the highest amount of residual endodontic material when compared to the other thirds; the difference was statistically significant, thus corroborating the results by Kaled et al 8 in 2011, Somma et al 16 in 2008, and Reddy et al 26 in 2011, who reported more debris at the apical root third regardless of the 27 in 2010 that found that the best cleaning was accomplished at the cervical third followed by the middle and apical thirds. They attributed this result to the dental anatomy of this site.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results demonstrate that the apical third had the highest amount of residual endodontic material when compared to the other thirds; the difference was statistically significant, thus corroborating the results by Kaled et al 8 in 2011, Somma et al 16 in 2008, and Reddy et al 26 in 2011, who reported more debris at the apical root third regardless of the 27 in 2010 that found that the best cleaning was accomplished at the cervical third followed by the middle and apical thirds. They attributed this result to the dental anatomy of this site.…”
Section: Discussionsupporting
confidence: 90%
“…These differences are most likely attributable to the design of the instruments, as D1, D2 and D3 are made of Ni-Ti and have three progressive tapers and lengths that fit the portions of the cervical, middle and apical root third, respectively. 2,3,7 According to reports by Giuliani et 26 in 2011 and Siotia 28 in 2011, none of the tested techniques leave root canals completely free of gutta-percha and sealer. We obtained similar results in this study.…”
Section: Discussionmentioning
confidence: 98%
“…The results presented in the second part of this study on the effectiveness of reciprocating instruments in reducing the amount of filling material are in agreement with the results of previous studies, showing that these instruments, although efficient, are incapable of completely removing the filling material from inside the canals, especially in the apical third REDDY et al, 2011;RÖDIG et al, 2014).…”
Section: Acknowledgmentssupporting
confidence: 91%
“…Furthermore, clinicians often forget that even though the roots may appear straight on a radiograph, curvatures in the third dimension are quite common. 2 Specific rotary NiTi file designs for root filling material removal are the ProTaper Universal Rotary Retreatment System (PTUS, DentsplyMaillefer, Ballaigues, Switzerland). The manufacturers claim that this systems, in addition to shaping and finishing the root canal, is also effective in the removal of the root filling material from root canals.…”
Section: Dental Journalmentioning
confidence: 99%
“…1 Elimination of these etiologies is essential to reestablish an environment conducive to repairing and healing. 2 The endodontic failure cases can be treated in three ways: nonsurgical retreatment, surgical retreatment, or extraction. Among all these treatment alternatives nonsurgical retreatment should be considered as the first choice of treatment.…”
Section: Introductionmentioning
confidence: 99%